The Impact of Teachers' Emotional Intelligence on Conflict Management in the Classroom: A Literature Study - Berlianti, Reri; Robinson, Adio; Rahmadani, Feny; Husnaini, Rafnil (PPSDP International Journal of Education, 2025)
The purpose of this study is to analysed the influence of teachers’ Emotional Intelligence (EI) on conflict management in the classroom. This study uses a literature review approach as the main method to collect, analysed, and synthesize information relevant to the topic of the influence of teachers’ emotional intelligence on conflict management in the classroom. It was found that teachers with high EI can recognize and manage emotional dynamics in the classroom. They are more effective in detecting potential conflicts, understanding students’ emotional needs, and designing strategies to manage behaviour. This supports the creation of an inclusive, productive, and low-stress learning environment. Teachers who can regulate their emotions tend to make wise decisions, reduce tension, and encourage harmonious conflict resolution. EI training has been shown to improve conflict management skills. Programs such as the RULER Approach are effective in creating a healthier educational ecosystem by reducing conflict in the classroom and improving the quality of learning.